Interaction between electrical storm and left ventricular ejection fraction as predictors of mortality in patients with implantable cardioverter defibrillator: A Chinese cohort study - Zhai, Zhengqin; Zhao, Shuang; Li, Xiaoyao; Chen, Keping; Xu, Wei; Hua, Wei; Su, Yangang; Tang, Min; Li, Zeyi; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2022)
Aims To determine the interaction of electrical storm (ES) and impaired left ventircular ejection fraction (LVEF) on the mortality risk of patients with implantable cardioverter defibrillator (ICD). Methods and Results A total of 554 Chinese ICD recipients from 2010 to 2014 were retrospectively included and the mean follow-up was 58 months. The proportions of dilated cardiomyopathy and the hypertrophic cardiomyopathy were 26.0% (144/554) and 5.6% (31/554), respectively..There were 8 cases with long QT syndrome, 6 with arrhythmogenic right ventricular cardiomyopathy and 2 with Brugada syndrome. Patients with prior MI accounted for 15.5% (86/554) and pre-implantation syncope accounted for 23.3% (129/554). A total of 199 (35.9%) patients had primary prevention indications for ICD therapy.Both ES and impaired LVEF (< 40%) were independent predictors for all-cause mortality (hazard ratio (HR) 2.40, 95% CI 1.57-3.68, P < 0.001; HR 1.94, 95% CI 1.30-2.90, P = 0.001, respectively) and cardiovascular mortality (HR 4.63, 95% CI 2.68-7.98, P < 0.001; HR 2.56, 95% CI 1.47-4.44, p = 0.001, respectively). Compared with patients with preserved LVEF (≥ 40%) and without ES, patients with impaired LVEF and ES had highest all-cause and cardiovascular mortality risks (HR 4.17, 95% CI 2.16-8.06, P < 0.001; HR 11.91, 95% CI 5.55-25.56, P < 0.001, respectively). In patients with impaired LVEF, ES increased the all-cause and cardiovascular mortality risks (HR 1.84, 95% CI 1.00-3.37, P = 0.034; HR 4.86, 95% CI 2.39-9.86, P < 0.001, respectively). In patients with ES, the deleterious effects of impaired LVEF seemed confined to cardiovascular mortality (HR 2.54, 95% CI 1.25-5.14, p = 0.038), and the HR for all-cause mortality was not significant statistically (HR 1.14, 95% CI 0.54-2.38, P = 0.735). Conclusion Both ES and impaired LVEF are independent predictors of mortality risk in this Chinese cohort of ICD recipients. The interaction of ES and impaired LVEF in patients significantly amplifies the deleterious effects of each other as distinct disease.